ANALYSIS OF THE EFFECT OF SEA SURFACE TEMPERATURE ON SEA LEVEL RISE IN INDONESIA DURING IN THE MID-HOLOCENE PERIOD AND THE FUTURE - Shafira Milennianti, Nabilah
Sea level rise in the modern era is influenced by climate change due to steric factors. In this study a comparison was made between sea surface temperature (SST) and sea level height (SSH) in Indonesia in the Mid-Holocene (MH), Pre-Industrial (PI), and future (FU) periods in 2300. with Representative Concentration Pathways (RCP) 8.5 using the Community Climate System Model version 4 (CCSM4). The results show that the average SST value is lower in the Mid-Holocene with a change in values of around -1°C in the MAM season and increases to the future by around 2°C, while the average value of SSH is lower in the Mid-Holocene with a change in values of around -0.1 m in the SON season in West Sumatra and increases in the future in the SON season by around 0.1 m in North Papua. The average correlation between the two parameters is a positive correlation of 0.55 (MH-PI) and 0.8 (FU-PI). The average rate of sea level change in Indonesia tends to be faster at FU-PI (around 0.0074 mm/year) than MH-PI (around -0.0022 mm/year). SST and SSH climatological patterns in West Sumatra, Banda Sea, and North Papua show a decrease in SST and SSH during the JJA season and an increase in SST and SSH during the SON season. This caused by a lag in insolation or the winter remnant effect. Signal analysis with Fourier transform shows that the dominant signal spectrum for changes in SST and SSH is caused by annual and semi-annual periodicity for the three areas. There is a fairly high interannual periodicity but not dominant so that interannual is a supporting factor influencing changes in SST and SSH in Indonesia.